Marketing Communication Model of Komodo Island in Indonesia (In the Study of Elaboraton Likelihood Model) - Arfika Pertiwi Putri (Jurnal Audience: Jurnal Ilmu Komunikasi, 2021)
Abstract Tourism is one of the sources of national income. Komodo Island is one of Indonesia's priority destinations. Moreover, Komodo Island is one of the products in which the Indonesian people are highly involved. In the pandemic era, tourism activities including Komodo Island have decreased. The purpose of this research was to determine an effective marketing communication model for Komodo Island in carrying out post-pandemic activities in increasing interest in returning to Komodo Island. This research used Partial Least Square (PLS) analysis, involving 100 Indonesian travelers as samples, used the Elaboration Likelihood Model (ELT) theory and message composition theory for basic analysis. This research result are the marketing communication model for Komodo Island is the way the central route operates in the ELT. The effectiveness of marketing communication included the elements of communication tools, types of arguments, and message quality. Repetition in this model was not an important aspect, while prior knowledge and strategies for message acquisition were important. The internal motivation was a variable that became important for achieving tourists’ satisfaction and interest in repeated visits.  Keywords: ELT; Komodo Island; Marketing Communication; Messages; Model  Abstrak  Pariwisata merupakan salah satu sumber pendapatan negara. Saat ini di era pandemic terjadi penurunan kegiatan pariwisata termasuk di Pulau Komodo. Pulau Komodo adalah salah satu destinasi prioritas Indonesia. Terlebih pulau Komodo merupakan salah satu product high involvement untuk masyarakat Indonesia. Untuk itu penelitian ini dilakukan guna mengetahui model marketing komunikasi efektif destinasi Pulau Komodo sehingga setelah pandemic dapat dilakukan serangkaian kegiatan guna meningkatkan kembali minat kunjung ulang ke Pulau Komodo. Penelitian ini menggunakan analisis PLS melibatkan 100 sample dengan teori Elaboration Likelihood Model (ELT) dan teori penyusunan pesan. Penelitian ini menunjukkan bahwa model marketing komunikasi destinasi Pulau Komodo merupakan cara kerja central rute dalam ELT. Efektivitas marketing komunikasi terdiri dari elemen tools komunikasi, tipe argument dan kualitas pesan. Pengulangan dalam model ini bukan merupakan bagian yang penting namun pengetahuan utama dan strategi pemenuhan perolehan pesan merupakan elemen konstruksi yang penting. Motivasi internal merupakan variable yang menjadi penting untuk mencapai kepuasan wisatawan dan minat kunjung ulang.  Kata kunci: ELT; Marketing Komunikasi; Model; Pesan ; Pulau Komodo